Safety and efficacy of p38 mitogen-activated protein kinase inhibitors (MAPKIs) in COPD - Yu, Haichuan; Su, Xiaojie; Lei, Ting; Zhang, Lu; Feng, Zhouzhou; Zhang, Chuchu; Zhang, Meng; Wang, Yalei; Chen, Xinlong; Liu, Jian (Frontiers in Pharmacology, 2022)
Introduction: Chronic inflammation is the core mechanism of the development of chronic obstructive pulmonary disease (COPD). Corticosteroid resistance in COPD limits its anti-inflammatory potency. p38 MAPKIs were suggested as an alternative to corticosteroids despite the fact that there is currently no systematic review evaluating existing evidence. Methods: This randomized controlled trials (RCT)-based systematic review with meta-analysis was conducted following the PRISMA statement. RCTs were searched and screened from 8 databases. Three types of data, including basic information of included studies, pre-defined outcome data, and quality assessment information were extracted. Pooling values and associated 95 % confidence intervals were deemed as statistically significant only when two-tailed p values were smaller than 0.05. Results: This study included 10 RCTs with a total population of 1,751 [age, mean (SD) = 64.39 (8.06)]. Safety and several efficacy indicators of lung function, inflammatory biomarkers, and quality of life were meta-analyzed. Despite the improvement of post-bronchodilator-forced vital capacity (FVC), no difference between p38 MAPKIs and placebo was found in both safety and efficacy. Conclusion: Compared with placebo, p38 MAPKIs are safe but did not show any significant effects in the COPD population. Results of this study should be regarded with caution due to the small number of included studies and heterogeneity from combining different p38 MAPKIs as a whole. Systematic Review registration: PROSPERO #CRD42022302890.